Cellular Vehicle-to-Everything (C-V2X) - System architecture and specifications - Mohd Zamri, Ibrahim (Malaysian Technical Standards Forum Bhd (MTSFB), 2025)
This technical code for Cellular Vehicle-to-Everything (C-V2X) System Architecture and Specifications (‘this Technical Code’) was developed pursuant to Section 185 of the Communications and Multimedia Act 1998 (Laws of Malaysia Act 588) by the International Mobile Telecommunications and Future Networks Working Group of the Malaysian Technical Standards Forum Bhd (MTSFB).